Pengaruh Perbankan Syariah Terhadap Financial Deepening Di Indonesia dengan Inflasi Sebagai Variabel Moderating - Miranda Miranda; Iqbal Rafiqi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This research examines the effect of third party funds and sharia financing on financial deepening in Indonesia by highlighting inflation as a moderating variable. Researchers used panel data namely data obtained from several financial report for 2017-2021 from 3 islamic commercial banks, which are the sample of this research with quarterly data. The data analysis technique in the research used a panel data regression test (CEM) and a moderation test with the help of the eviews version 12 programs. The results of this research show that third party funds and sharia financing have an effect on financial deepening in Indonesia without being moderated by inflation. Meanwhile, inflation has no effect on financial deepening in Indonesia. The research results imply that sharia banking will expand services to the community with the aim of increasing sharia bank capital for financing. This research contributes to the scientific horizon of Islamic banking and the role of financial deepening in terms of the financiak sector.